PENGGUNAAN MODEL PROTON DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS, KERJA SAMA DAN HASIL BELAJAR SISWA: indonesia - Muhammad Rijali Hadi; Ahmad Suriansyah; Ratna Purwanti (STKIP Subang, 2025)
The purpose of this study was to describe teacher and student activities, and to analyze the improvement of critical thinking skills, cooperation skills, and student learning outcomes. The problem in this study is the low activity of teachers and students in learning, critical thinking skills and student cooperation in science content. Efforts made to deal with this problem are the use of the PROTON learning model and Wordwall Media in the learning process. This study applies Classroom Action Research (CAR) which is carried out in 4 meeting sessions. The research subjects consisted of 17 fourth grade students at SDN Asam Pauh, consisting of 10 male students and 7 female students in the odd semester of the 2024/2025 academic year. The results of this study indicate that the application of the PROTON model and Wordwall media can improve teacher activity, student activity, critical thinking and cooperation skills, and student learning outcomes. The results of this study are recommended for principals, teachers, and further researchers as an alternative to using innovative learning models to improve the quality of education